An Investigation of the Mechanisms of Technology Transfer and Automation in Universities: A Case Study on Promoting Entrepreneurship and Startup Ecosystems at Bangladesh Open University (American Journal of Education and Technology, 2024)
This study conducts a thorough analysis of the processes involved in technology transfer, automation, and entrepreneurship at Bangladesh Open University (BOU), using a qualitative research methodology. The study utilizes thematic analysis, supported by NVivo, to extract valuable insights from interviews with 30 important stakeholders, including academics, students, and administrators. The results indicate moderate achievements in the transfer of technology, characterized by difficulties in commercializing university research and developing robust industry connections. Within the field of automation, the study emphasizes the important role it plays in improving access to education, while also acknowledging the difficulties created by limited digital skills and unequal distribution of resources. The expansion of the entrepreneurship ecosystem at BOU is clearly visible, but, it is limited by a requirement for stronger support systems, namely in the areas of mentorship and funding. These qualitative views provide a detailed and subtle viewpoint on how BOU aligns with or deviates from well-known ideas like the Triple Helix Model and Academic Entrepreneurship Theory. They emphasize the distinct problems and opportunities that arise in an open university environment. The study’s results make significant contributions to scholarly discussions, highlighting the importance of customized approaches in incorporating technology and fostering entrepreneurial growth in higher education, particularly in the context of developing nations.